Baltic Listed Companies´ disclosure quality – far ahead or lagging behind? - Karmo, Imbi; Laidroo, Laivi (Estonian Discussions on Economic Policy, 2014)
The objective of this paper is to determine the level of average quality of disclosures made in English by biggest companies listed on Baltic stock exchanges and to analyse it in the context of biggest companies listed on other Central and Eastern European (CEE) and three developed European (EU) stock exchanges. Content analysis reveals that the disclosure quality level of Baltic listed companies outperforms that of other CEE peers by at least 30% and in the context of stock exchange web page disclosures 50 to 80%. Compared to companies listed on developed EU stock exchanges, the disclosure quality of Baltic listed companies is slightly lower in the company home page category, however, it outperforms in the context of stock exchange web page disclosures. This result raises concerns about possibly too restrictive stock exchange web page disclosure regulations which may have a negative impact on the future outlook of Baltic stock exchanges.